1993
DOI: 10.1111/j.1467-8454.1993.tb00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Wage Differentials and the Role of Self‐employment in Australia*

Abstract: I am grateful for the substantial funding furnished by the Australian Research Council in support of this research project. I would like to acknowledge the excellent research assistance provided by Lindsay Binning. Thanks are due to Harry Bloch, Bruce Chapman, Peter Dolton, Paul Miller, J. Nevile and Mark Stewart. I am also grateful for detailed comments from two anonymous referees. 92 1993 IMMIGRANT WAGE DIFFERENTIALS AND THE ROLE OF SELF-EMPLOYMENT 93 AUSTRALIAN ECONOMIC PAPERS JUNE t=: + Log-Likelihood(0) =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 23 publications
6
69
0
1
Order By: Relevance
“…But in theory, the effects of age on self-employment choice also has two aspects, on the one hand, the growth of the age for the more entrepreneurial experience accumulation, is more conducive to self-employment activities; the increase of age, on the other hand, the general risk preference is lower, engaged in self-employment proportion will decline. Kidd are analyzed, the structure that is more likely to be nonlinear relationship between age and the self-employment, into the age of the self-employment peak between the ages of 35 to 44 [9]. With previous year employment as explanatory variables, got similar results.…”
Section: Personal Characteristicssupporting
confidence: 51%
“…But in theory, the effects of age on self-employment choice also has two aspects, on the one hand, the growth of the age for the more entrepreneurial experience accumulation, is more conducive to self-employment activities; the increase of age, on the other hand, the general risk preference is lower, engaged in self-employment proportion will decline. Kidd are analyzed, the structure that is more likely to be nonlinear relationship between age and the self-employment, into the age of the self-employment peak between the ages of 35 to 44 [9]. With previous year employment as explanatory variables, got similar results.…”
Section: Personal Characteristicssupporting
confidence: 51%
“…Considering the theoretical rationale, the operational model depends upon the factors which are provided by the data. Generally, we have found in the past studies in the self-employment literature (e.g., Rees and Shah, 1986, Borjas, 1987, Evans, 1989, de Wit, 1993, Bernhardt, 1994, Kidd, 1993) that self-employment is determined by both human capital and non-human capital variables which are discussed below. The justification for including these variables in the women self-employment model and their expected relationships are interpreted below.…”
Section: Variables Descriptionmentioning
confidence: 95%
“…So, it is not surprising that various studies have concluded mixed effects of educational attainment on self-employment. Kidd (1993) has concluded that tendency to be self-employed is not significantly influenced by the educational attainment. Further, according to Evans' (1989) study, it is found that self-employment is inversely and significantly influenced by the level of education among immigrants.…”
Section: Variables Descriptionmentioning
confidence: 99%
“…The approach is based on the estimation of two separate earnings equations for each group, which are then used in the estimation of the wage gap due to differences in observed characteristics (explained part) and due to differences in coefficients which is referred as discrimination (see e.g. Kidd, 1993;Golder, 2000;Nielsen, 2000;Nielsen et al, 2004;Aldashev et al, 2008) …”
Section: Discriminationmentioning
confidence: 99%